Genome analysis of Kutzneria sp. strain BCCO 10_1627 and detection of antifungal secondary metabolites - Jernej, Linda (Jihočeská univerzita, 2019)
Secondary metabolites, produced by various microbes, are used since decades for treatment of diseases. The bacterial genus Kutzneria is known for synthesizing compounds with antifungal activity, which might be used against pathogenic fungi, causing agricultural relevant diseases. This thesis deals with the genome analysis of the strain Kutzneria sp. BCCO 10_1627 for prediction of secondary metabolite gene cluster. Moreover, the antifungal activity of the strain was determined experimentally.
Genome analysis of Kutzneria sp. strain BCCO 10_1627 and detection of antifungal secondary metabolites